2017
DOI: 10.12775/cjfa.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

Risky Risk Measures: A Note on Underestimating Financial Risk Under the Normal Assumption

Abstract: This note compares three different risk measures based on the same stock return data: (1) the portfolio variance as in Markowitz (1952), (2) the value at risk based on the historical return distribution, and (3) the value at risk based on a t copula. Unless return series follow a Normal distribution, Normal-based risk measures underestimate risk, particularly so during periods of market stress, when accurate risk measurement is essential. Based on these insights, we recommend that supervisors discontinue to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is also a supplement to the VaR LPM and applies specifically to the left tale of a distribution of the VaR. It can be the average across all negative deviations from the VaR or the variance of the negative deviations of a pre-defined VaR It is, therefore, a method that places heavier weight on larger deviations from the current VaR in comparison to the smaller deviations (Goodfellow and Salm 2016). An investor can select or set the risk-free rates, and by selecting the degree of the moment, one can specify the risk levels that suit the portfolio or risk needs.…”
Section: Suggested Alternatives For Non-normal Distributions-unconditional Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a supplement to the VaR LPM and applies specifically to the left tale of a distribution of the VaR. It can be the average across all negative deviations from the VaR or the variance of the negative deviations of a pre-defined VaR It is, therefore, a method that places heavier weight on larger deviations from the current VaR in comparison to the smaller deviations (Goodfellow and Salm 2016). An investor can select or set the risk-free rates, and by selecting the degree of the moment, one can specify the risk levels that suit the portfolio or risk needs.…”
Section: Suggested Alternatives For Non-normal Distributions-unconditional Distributionsmentioning
confidence: 99%
“…An investor can select or set the risk-free rates, and by selecting the degree of the moment, one can specify the risk levels that suit the portfolio or risk needs. Goodfellow and Salm (2016) compared three different risk measures based on the same stock return data, the portfolio variance as in the seminal works of Markowitz (1952) and the VaR based on t copula. They concluded that normal assumption substantially underestimates the risk faced by an organization, and therefore, they discredited the use of risk measures based on normal assumption.…”
Section: Suggested Alternatives For Non-normal Distributions-unconditional Distributionsmentioning
confidence: 99%